2021
DOI: 10.1007/s00453-020-00785-5
|View full text |Cite
|
Sign up to set email alerts
|

Travelling on Graphs with Small Highway Dimension

Abstract: This is a repository copy of Travelling on graphs with small highway dimension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…These structural properties were also leveraged by Becker et al [6] who gave a PTAS for the Bounded-Capacity Vehicle Routing problem, and a parameterized approximation scheme for the k-Center problem (which is essentially k-Clustering q with q = ∞) and k-Median. In the lower bound side, Disser et al [12] showed that Steiner Tree and TSP are weakly NP-hard even when the highway dimension is 1, i.e., each of them is NP-hard but an FPTAS exists for graphs of highway dimension 1.…”
Section: Our Resultsmentioning
confidence: 99%
“…These structural properties were also leveraged by Becker et al [6] who gave a PTAS for the Bounded-Capacity Vehicle Routing problem, and a parameterized approximation scheme for the k-Center problem (which is essentially k-Clustering q with q = ∞) and k-Median. In the lower bound side, Disser et al [12] showed that Steiner Tree and TSP are weakly NP-hard even when the highway dimension is 1, i.e., each of them is NP-hard but an FPTAS exists for graphs of highway dimension 1.…”
Section: Our Resultsmentioning
confidence: 99%
“…These structural properties were also leveraged by Becker et al [8] who gave a PTAS for the Bounded-Capacity Vehicle Routing problem, and a parameterized approximation scheme for the k-Center problem (which is essentially k-Clustering q with q = ∞) and k-Median. In the lower bound side, Disser et al [15] showed that Steiner Tree and TSP are weakly NP-hard even when the highway dimension is 1, i.e., each of them is NP-hard but an FPTAS exists.…”
Section: Related Workmentioning
confidence: 99%
“…For Bounded-Capacity Vehicle Routing a PTAS was shown [10], and the same work also gives approximation schemes for the k-Median and k-Center problems, when parameterizing by k and the highway dimension. The k-Center problem is hard even in the parameterized setting [23,24], and Traveling Salesperson was recently shown [20] to be weakly NP-hard even if the highway dimension is 1. It is an intriguing question whether the problems studied in this paper also admit PTASs for low highway dimension graphs.…”
Section: On Highway Dimensionmentioning
confidence: 99%